Support System of Quality Control for XYZ Company using PHP Laravel and React Native - Christoper Marchiato; Wella Wella (Universitas Islam Raden Rahmat, Malang, 2024)
XYZ Company is a manufacturing company that makes diesel products. In the production process, there is a need for quality control so that the final product can meet the company's quality standards. The problem of the XYZ Company is the quality control process carried out by the company that still uses manual so that a lot of paper is wasted in the quality control process.The design and construction process carried out is using the waterfall method. The waterfall method consists of five steps is requirements, design, implementation, verification and maintenance. The framework for implementation process on the website is Laravel, and the CSS used is Tailwind CSS, and the framework for application is react native. The system that has been designed has succeeded in providing convenience in quality control.